I think you meant to put parentheses around (x+h) and not the whole fraction.
(1/(x+h) +1/x) / x
First start with the top by getting a common denominator.
1/(x+h) + 1/x
= x/[x(x+h)] + (x+h)/[x(x+h)]
= (x +x+h) / [x(x+h)]
= (2x+h) / [x(x+h)]
The last step is to divide by x.
((2x+h) / [x(x+h)]) / x
= ((2x+h) / [x(x+h)]) (1/x)
= (2x+h) / [x^2 (x+h)]
Remove the parentheses around 1/x+h, they are useless.
1/x + 1/x = 2/x, so...
Dividing by x is the same as multiplying by 1/x. So multiply each term in the numerator by 1/x, to get rid of that ugly double fraction. Your final answer is...
2/x^2 + h/x
( 2x+h ) / x = 2 + (h / x)
get rid of the brachets first and keep doing it until there are no brachets that makes it easier
Add (1/x+h)= Result#1
Now add (Result#1) +(1/x)= Result#2
Hint: common denominators!
This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.
More Questions & Answers...